The Olfactory Tract: Basis for Future Evolution in Response to Rapidly Changing Ecological Niches - Whitlock, Kathleen E.; Palominos, M. Fernanda (Frontiers in Neuroanatomy, 2022)
Within the forebrain the olfactory sensory system is unique from other sensory systems both in the projections of the olfactory tract and the ongoing neurogenic potential, characteristics conserved across vertebrates. Olfaction plays a crucial role in behaviors such as mate choice, food selection, homing, escape from predators, among others. The olfactory forebrain is intimately associated with the limbic system, the region of the brain involved in learning, memory, and emotions through interactions with the endocrine system and the autonomic nervous system. Previously thought to lack a limbic system, we now know that teleost fishes process emotions, have exceptional memories, and readily learn, behaviors that are often associated with olfactory cues. The association of neuromodulatory hormones, and more recently, the immune system, with odor cues underlies behaviors essential for maintenance and adaptation within natural ecological niches. Increasingly anthropogenic perturbations affecting ecosystems are impacting teleost fishes worldwide. Here we examine the role of the olfactory tract as the neural basis for the integration of environmental cues and resulting behaviors necessary for the regulation of biotic interactions that allow for future adaptation as the climate spins out of control.